Determination of Metallothionein, Malondialdehyde, and Antioxidant Enzymes in Earthworms (Eisenia fetida) Following Exposure to Chromium. (23rd July 2016) - Gao, Chao; Xu, Jingbo; Li, Ji; Liu, Zhengtao
ABSTRACT: Here is reported the effect of chromium on the toxicological response of earthworms Eisenia fetida . Laboratory acclimated E. fetida were exposed to chromium for 1, 3, 7, and 14 days and the concentrations of metallothionein, malondialdehyde, superoxide dismutase, catalase, and peroxidase were determined. The results demonstrated that the concentrations of metallothionein and malondialdehyde increased with chromium dosage and time. The activities of superoxide dismutase and catalase increased after the introduction of chromium, while the activity of peroxidase was lower than the control group. Enhancement and inhibition mechanisms are suggested for superoxide dismutase, catalase, and peroxidase, indicating that together they protect membrane lipids from oxidative stress. Metallothionein and malondialdehyde were sensitive to chromium concentration, indicating that they may be regarded as biomarkers for monitoring applications.